2009
DOI: 10.1002/gcc.20723
|View full text |Cite|
|
Sign up to set email alerts
|

Genomic alterations in histopathologically normal breast tissue from BRCA1 mutation carriers may be caused by BRCA1 haploinsufficiency

Abstract: Multiple biopsies of normal breast tissue from 10 BRCA1 mutation carriers have been analyzed using array-based comparative genomic hybridization. Normal breast tissue from five age-matched control subjects without a family history of breast cancer was included for reference purposes. We repeatedly found multiple low copy number aberrations at a significantly higher frequency in histopathologically normal tissue from BRCA1 mutation carriers than in normal control tissue. Some of these aberrations were similar a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Samples of histologically normal breast tissue were collected from women who had undergone a prophylactic mastectomy due to increased risk of developing breast cancer (see Rennstam et al [13] for details). Informed consent forms were signed by all women included in the study and the study was approved by the ethics committee at Lund University, Sweden.…”
Section: Resultsmentioning
confidence: 99%
“…Samples of histologically normal breast tissue were collected from women who had undergone a prophylactic mastectomy due to increased risk of developing breast cancer (see Rennstam et al [13] for details). Informed consent forms were signed by all women included in the study and the study was approved by the ethics committee at Lund University, Sweden.…”
Section: Resultsmentioning
confidence: 99%
“…However, our findings do not support the general assumption and previous findings reported in the literature that BRCA promoter methylation and BRCA germline mutations are mutually exclusive. In most studies, none of the BRCA -related breast carcinomas showed BRCA promoter methylation [16, 21, 2326]. Kontorovich et al [20] observed BRCA1 promoter methylation in 3 (6.3%) of 48 BRCA1 -related breast carcinomas, and Tapia et al [17] observed BRCA1 promoter methylation in 2 (66.7%) of 3 observed BRCA1 -related breast carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…Haploinsufficiency was also involved in impaired differentiation of epithelial luminal cells, leading to an expanded luminal progenitor population in BRCA1 mut/+ breast tissues [40]. All these data are consistent with the assumption that BRCA1 mut/+ breast cells are likely to cumulate genomic aberrations during mitotic recombination [38]. Higher proliferative rates caused by the hormone signaling in these cells would therefore explain the sex and organ-specific penetrance of BRCA1 -related cancers.…”
Section: Discussionmentioning
confidence: 55%
“…Since BRCA1 is involved in DNA repair and cell cycle control, our results suggest that E2 and P4 exposure may enhance proliferation in BRCA1 mut/+ breast tissues, and potentially increase the accumulation of unrepaired mutations and DNA lesions. Indeed, previous studies have shown that BRCA1 mut/+ epithelial breast cells were haploinsufficient for BRCA1 as they displayed genomic alterations [38, 39], including defects in stalled replication fork repair and a higher frequency in fork collapses [39]. Haploinsufficiency was also involved in impaired differentiation of epithelial luminal cells, leading to an expanded luminal progenitor population in BRCA1 mut/+ breast tissues [40].…”
Section: Discussionmentioning
confidence: 99%